2022
DOI: 10.3389/fpsyt.2022.817716
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Psychological Health on Patient Recovery After Arthroplasty

Abstract: PurposeThe purpose of this study was to determine the relationship between psychological health and postoperative recovery and satisfaction in patients undergoing total joint arthroplasty (TJA).MethodsWe prospectively enrolled patients undergoing TJA from July 2019 to December 2020. A psychological evaluation was conducted according to the Hospital Anxiety and Depression Scale (HADS). Based on the preoperative HADS scores, we grouped the patients into two groups: the symptomatic group and the asymptomatic grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Similarly, the positive correlation between ankle dorsiflexion and HADS Anxiety at the 2-month mark highlights the intricate relationship between physical recovery and psychological well-being. These findings are in line with current literature which emphasizes the holistic nature of patient recovery, suggesting that physical improvements post-surgery can have far-reaching effects on mental health and overall quality of life [40,41]. The correlation analysis in our study not only confirms these established notions but also provides a nuanced understanding of how specific clinical interventions like screw removal in tibiofibular diastasis can influence various dimensions of patient health.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, the positive correlation between ankle dorsiflexion and HADS Anxiety at the 2-month mark highlights the intricate relationship between physical recovery and psychological well-being. These findings are in line with current literature which emphasizes the holistic nature of patient recovery, suggesting that physical improvements post-surgery can have far-reaching effects on mental health and overall quality of life [40,41]. The correlation analysis in our study not only confirms these established notions but also provides a nuanced understanding of how specific clinical interventions like screw removal in tibiofibular diastasis can influence various dimensions of patient health.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have reported that patients with preoperative psychological distress are more likely to experience poor outcomes after joint replacement, such as reduced function and higher rates of revision surgery [ 14 , 15 , 16 , 17 , 18 ]. However, the role of psychological factors in predicting outcomes after PAO, particularly in relation to differences in outcomes between PAO for hip dysplasia and PAO for acetabular retroversion, has mainly be unaccounted for in the literature [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since acupuncture operations cannot be blinded to patients, the principle of triple separation of clinical operators, efficacy evaluators, and statistical analysts can be utilized. (2) The risk of bias assessment of the included studies was mostly unclear, and the quality of the literature was low. Therefore, in future studies, reporting should be based on the Consolidated Standards of Reporting Trials (CONSORT) to ascertain the literature quality (147).…”
Section: Discussionmentioning
confidence: 99%
“…TKA, a well-established and effective reconstructive treatment, has demonstrated long-term efficacy in managing severe multi-compartmental knee osteoarthritis with deformity. When compared to basic treatment, pharmacological intervention, and reparative approaches for KOA, TKA demonstrates significant improvements in pain relief and joint function ( 2 ), Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) scores, hospital for special surgery knee score (HSS), and overall quality of life during long-term follow-up.…”
Section: Introductionmentioning
confidence: 99%